RISE: IWK-UiTM research collaboration / Assoc. Prof. Dr Aidah Jumahat - Jumahat, Aidah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Indah Water Knosortium (IWK) Sdn. Bhd. is Malaysia's national sewerage company which has been entrusted with developing and maintaining a modern and efficient sewerage system for all Malaysians.